1991
DOI: 10.3109/15368379109031397
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Electric Charges Carried by Bees: Evidence of Biological Variations

Abstract: SVarious insects, especially social insects, possess electric charges. Erickson (1982,1983) shows their involvement in the odor receptor efficiency of honey bee antenna. Also, the author suggests the importance of charges in the transfer of pollen grains from flowers to pollinator insects. To measure directly electric charges, we fit a sensor used to determine the charges of raindrops. Strongly clustered wintering bees and foraging bees were rne.asured. The individual values range between -4OOpC to +600pC (m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 15 publications
3
30
0
1
Order By: Relevance
“…Bees accumulate charge during motion through their environment, (14,17). A similar phenomenology likely applies to other flying or walking insects (18,19).…”
Section: Minimum Electric Field Strengths Required To Elicit Electrommentioning
confidence: 88%
See 1 more Smart Citation
“…Bees accumulate charge during motion through their environment, (14,17). A similar phenomenology likely applies to other flying or walking insects (18,19).…”
Section: Minimum Electric Field Strengths Required To Elicit Electrommentioning
confidence: 88%
“…Only when the bee's charge was deliberately set to zero, did the antennae respond to a lower voltage than the hair. In natural free-flight situation, however, bees are only rarely found with zero charge (15,17).…”
Section: Significancementioning
confidence: 99%
“…In insects, the wax layer of the exocuticle causes a high electrical resistance between the inner and outer parts of the body, and along the body surface leading to charge accumulation when insects walk or fly [3][4][5]. It is now clear that surface charge in insects is a biological phenomenon reflecting their movements and the movements of their body parts [6]. It is also clear that insects respond to electric fields, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These fields may also alter the behaviour of the bee parasite Varroa jacobsoni, and can assist their attack by attraction of the parasite to the charged bee [2]. Other studies have suggested that accumulation of charge during flight could assist foraging and pollination through the transfer of pollen grains onto plant stigmata [3][4][5]. Static electric fields can also lead to changes in walking [6,7] and avoidance behaviour [6,8], and influence locomotion and agitation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%